2021
DOI: 10.1029/2020jd033778
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐Regional Transport of Haze Particles From the North China Plain to Yangtze River Delta During Winter

Abstract: Because of the rapid development of urbanization and industrialization and rise of economy, China has frequently experienced haze pollution. These haze pollution events profoundly affect human health, such as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 114 publications
2
29
0
Order By: Relevance
“…Compared with the pre-LCD period, the average concentration of SO 2 and NO 2 reduced by 36.4 % and 70.4 % during the LCD, but increased significantly to 9.7 ± 9.1, 35.6 ± 19.9 μg m −3 ( Table 1 ), due to the recovery of industrial production during the post-LCD ( Li et al, 2020a ; Pei et al, 2020 ). As an important tracer of primary combustion emissions ( Zhang et al, 2021 ), CO presented a decreasing trend similar to that of PM 2.5 concentration throughout the LCD ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 82%
“…Compared with the pre-LCD period, the average concentration of SO 2 and NO 2 reduced by 36.4 % and 70.4 % during the LCD, but increased significantly to 9.7 ± 9.1, 35.6 ± 19.9 μg m −3 ( Table 1 ), due to the recovery of industrial production during the post-LCD ( Li et al, 2020a ; Pei et al, 2020 ). As an important tracer of primary combustion emissions ( Zhang et al, 2021 ), CO presented a decreasing trend similar to that of PM 2.5 concentration throughout the LCD ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 82%
“…In recent studies, however, the roles of primary aerosol components are also reported in association with LRT process. For example, the effects of primary aerosols (i.e., high BC) on meso-scale meteorological condition in North China Plain and Yangtze River delta in China 55 , and also their association with secondary aerosol formations via heterogeneous reaction process 56 during the long-range transport episodes in China. Such results are indicating the importance of aerosol chemical compositions over the exit area of LRT process, and suggesting that the well-characterized components and its interaction via radiative processes are together the key factors within clouds.…”
Section: Discussionmentioning
confidence: 99%
“…We also employed satellite observations, the Modern-Era Retrospective Analysis for Research and Applications, Version 2 (MERRA-2), to estimate and evaluate spatiotemporal trends of simulated PM 2.5 in Northeast Asia. MERRA-2 has a resolution of approximately 0.5° × 0.625° and 72 hybrid-eta levels from the surface to 0.1 hPa 55 . The reanalysis data is computed on a latitude–longitude grid at the same spatial resolution using a 3-D variation data assimilation (3DVAR) algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…PM2.5 during haze periods was 139.7 ± 47.2 µg m −3 , which was 2.7 times higher than that (52.0 ± 16.5 µg m −3 ) during clean periods. As a reliable primary combustion emission tracer (Zhang et al, 2021), CO exhibited strong positive correlations (R 2 = 0.77) (Fig. S1) with PM2.5 concentration.…”
Section: General Descriptions Of Carbonaceous Species In Pm25mentioning
confidence: 99%
“…EC is directly emitted from the incomplete combustion of fossil fuels and biomass (Shi et al, 2021). OC is not only from the primary emissions, but also is from the atmospheric chemical reactions (Zhang et al, 2014).…”
Section: General Descriptions Of Carbonaceous Species In Pm25mentioning
confidence: 99%